Creación de una radio bocina estudiantil con las niñas y niños de la Escuela Fiscal Mixta Fray Jodoco Ricke (Comuna Lumbisí) en base a la equidad de género, con el fin de entablar nuevos lazos comunicativos encauzados a prevenir la violencia contra la mujer. - García Castañeda, Enrique Alejandro (2014)
This analysis about the advertising discourse of TV wants to understand the relationship between, the economic system and the femininity`s stereotype that is used in the advertising that has been transmitted over the past three year in Quito. This advertising continues using the women in the role of a happy housewife in private places and with their families; and the other hand, this advertising uses a new women`s image: the modern woman, in public places and professional success. It isn´t an innocent situation, because the publicity changes for showing a kind of society: the society that the publicity is promoting. Understanding that the advertising is a common thing in the city, and, the advertising discourse has a regulatory function in a context,